2020
DOI: 10.1088/1361-665x/ab9e0f
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional flexible sensor array-based damage monitoring for switch rail using passive and active sensing

Abstract: A passive monitoring technique for switch rails will be very attractive because it does not require extra excitations and can realize large area monitoring. However, complex wheel-rail interactions and sparse sensors will affect the accuracy of local damage identification. In contrast, an active monitoring technique has high local damage quantification ability but has low efficiency for large area monitoring. This study firstly presents a combination of piezoceramic material Lead zirconate titanate (PZT) wafer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Validation is used to verify the results of the analysis 35 and to insure that these results are accurate. In order to perform this validation, approximately 110,000 defects were divided into two groupings; an analysis grouping and a validation grouping.…”
Section: Validationmentioning
confidence: 99%
“…Validation is used to verify the results of the analysis 35 and to insure that these results are accurate. In order to perform this validation, approximately 110,000 defects were divided into two groupings; an analysis grouping and a validation grouping.…”
Section: Validationmentioning
confidence: 99%
“…Applications of ultrasonic measuring techniques in railway systems have been widely seen covering active ultrasonic guided waves [24,25], passive acoustic emission [26][27][28], phased array [29], air-coupled ultrasonic testing [30], and emerging ultrasonic structural health monitoring (SHM) techniques [31][32][33]. On the other hand, some recent research works linking ultrasonic sensing with contact mechanics can be found in [34,35] by Song et al for bolt looseness monitoring based on fractal contact theory.…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al, [19] proposed a segmented principal component analysis method to extract the features of the signals collected by the sensors at different positions and used SVM to quickly classify the cracks, corrosion, transverse cracks and other defects on the rail head surface. Hu et al, [20] realised crack location monitoring of 14 mm at the bottom of the rail through active and passive UGWs. The aforementioned findings indicate that UGW technology has positive outcomes for rail crack monitoring.…”
Section: Introductionmentioning
confidence: 99%